A novel processing route to develop alumina matrix nanocompositesreinforced with multi-walled carbon nanotubes. (April 2015) - Yi, J.; Xue, W.J.; Xie, Z.P.; Chen, J.; Zhu, L.
Graphical abstract: Highlights: We reported a novel approach to fabricate CNTs/Al2 O3 nanocomposites. Functionalized multi-walled CNTs were used to improve the distribution of CNTs. Homogeneous distribution of CNTs in ceramic matrix has been achieved. A clear improvement in the fracture toughness was achieved after adding CNTs. Abstract: In the present work, we have reported a novel approach to fabricate carbon nanotubes (CNTs)/alumina nanocomposites with improved fracture toughness using a simple heterogeneous nucleation through the incorporation of functionalized multi-walled carbon nanotubes (MWCNTs). For this approach, homogeneous distribution of CNTs in ceramic matrix has been achieved up to 5.7 vol.% CNTs content, revealed by SEM observations of both composite powders and fracture surfaces of sintered specimens. Excellent comprehensive mechanical properties as high as 6.03 ± 0.45 MPa m 1/2 fracture toughness and 19.18 ± 0.33 GPa hardness are obtained in alumina nanocomposite with 5.7 vol.% MWCNTs fabricated via spark plasma sintering (SPS) with subsection pressure method, increasing 53% and 30% over that of pure alumina sintered under the same sintering condition, respectively. Furthermore, the fracture mode transition and the activated toughening mechanisms during crack propagation are taken into account to explain the improvement in fracture toughness.